Peach Leaf Extract (Prunus persica L.) Mitigates Metabolic Syndrome and Oxidative Stress in High-Fructose Diet Rats - Djihane Bali; Zoubida Mami-Soualem; Nabila Belyagoubi-Benhammou; Nassima Benzazoua; Chahrazed Belarbi; Youssouf Kachekouche; Waleed Aldahmash; Md Ataur Rahman; Abdel Halim Harrath (Plants)
This study aimed to evaluate the protective effects of peach leaf extract (Prunus persica L.) against metabolic syndrome and oxidative stress in Wistar rats subjected to a high-fructose diet. The Wistar rats were divided into groups and fed a high-fructose diet, with or without supplementation of peach leaf extract. The extract was characterized by its bioactive compounds, including an organic acid yield of 53.8%, total phenolic content (TPC) of 273.36 ± 1.929 mg GAE/g DW, flavonoid content (TFC) at 149.02 ± 57.47 mg QE/g DW, condensed tannins (TCT) at 2.34 ± 0.171 mg CE/g DW, and flavonols at 81.67 ± 0.497 mg DE/g DW. In vitro tests showed significant antioxidant potential, with a total antioxidant capacity (TAC) of 44.11 ± 6.328 mg AAE/g DW, DPPH radical scavenging activity (IC50 = 4.89 mg/mL), and reducing power assay (FRAP, IC50 = 0.525 mg/mL). The results indicated that the extract significantly reduced body weight gain, plasma insulin levels (0.30 ± 0.00 U(IU)/mL), glycemia (0.955 ± 0.068 g/L), total cholesterol (0.555 ± 0.177 g/L), and triglycerides (0.720 ± 0.141 g/L). Regarding oxidative stress markers, the extract decreased levels of malondialdehyde (MDA, 4567 ± 121 μmol/L), hydroperoxides (1304 ± 288 μmol/L), and carbonylated proteins (0.029 ± 0.020 μmol/L), while increasing levels of vitamin C (25.84 ± 3.00 mg AAE/L), Oxygen Radical Absorbance Capacity (ORAC, 6.043 ± 0.345 UA), and catalase activity (0.0052 ± 0.00008 μL/mL). These findings suggest that P. persica L. may alleviate impairments related to metabolic syndrome by improving metabolic profiles and reducing oxidative stress in rats fed a high-fructose diet, making it a potential dietary supplement for managing metabolic syndrome.